Publisher Correction: Multicolor multiscale brain imaging with chromatic multiphoton serial microscopy - Lamiae Abdeladim (Nature Portfolio, 2019)
Affiliation 4 incorrectly read ‘University of the Basque Country (Ikerbasque), University of the Basque Country and Donostia International Physics Center, San Sebastian 20018, Spain.’ Also, the affiliations of Ignacio Arganda-Carreras with ‘IKERBASQUE, Basque Foundation for Science, Bilbao, 48013, Spain’ and ‘Donostia International Physics Center (DIPC), San Sebastian, 20018, Spain’ were inadvertently omitted. Additionally, the third sentence of the first paragraph of the Results section entitled ‘Multicontrast organ-scale imaging with ChroMS microscopy’ incorrectly read ‘For example, one can choose lambda1 = 850 and lambda2 = 110 nm for optimal two-photon excitation of blue and red chromophores.’. The correct version reads ‘lambda2 = 1100 nm’ instead of ‘lambda2 = 110 nm’. These errors have now been corrected in the PDF and HTML versions of the Article.